Contra Latinos et Adversus Graecos : The Separation Between Rome and Constantinople from the Ninth to the Fifteenth Century - Calia, A. (Orientalia Lovaniensia Analecta Ser, 2020)
Intro -- Title page -- CONTENTS -- ABBREVIATIONS -- PREFACE -- CONTRA LATINOS ET ADVERSUS GRAECOS: AN INTRODUCTION -- BYZANTIUM AND THE PAPACY FROM THE FIFTH TO FIFTEENTH CENTURIES: THE THREE-STAGE RESPONSE -- LA PROCESSIONE DELLO SPIRITO SANTODA ORIGENE A GREGORIO DI NAZIANZO: LA TENSIONE ERMENEUTICANELLA DISCUSSIONE SUL FILIOQUE -- LA PROCESSIONE DELLO SPIRITO SANTONEL DE TRINITATE DI AGOSTINO -- THEOLOGICAL DISPUTE, LOGICAL ARGUMENTS: ON PHOTIOS' USE OF SYLLOGISMS AGAINST THE FILIOQUE IN THE MYSTAGOGIA -- DIONYSIUS LATINUS II: ANASTASIO IL BIBLIOTECARIO E LE IMPLICAZIONI POLITICO-ECCLESIASTICHE ECUMENICHEDELLE VERSIONES DIONYSII CAROLINGE -- ESPORTARE LE RIFORME. PRIMATO PAPALE ED ECCLESIOLOGIA NEI RAPPORTICON LA CHIESA GRECA TRA XI E XII SECOLO -- RESOLVING HUMBERT'S CRUX: ANTI-GREEK POLEMICS AND THE QUESTION OF CRUCIFIED SAINTS -- BYZANTINE ANTI-LATIN TEXTS AND THE BYZANTINE "ANTHOLOGICAL MENTALITY" -- THE REFUTATION OF PETRUS GROSSOLANUS: THE Λόγοι ἀντιρρητικοί BY EUSTRATIOS OF NICAEA -- Οὐ πρὸς ἔριν: ALCUNE CONSIDERAZIONI SUL PROLOGO AIDIALOGHI SULLA PROCESSIONE DELLO SPIRITO SANTODI NICETA «DI MARONEA»* -- THE LIBER DE VERA PHILOSOPHIA AND THE ROLE OF THE GREEK FATHERS IN THE PORRETANS* -- IL DE SANCTO ET IMMORTALI DEO DI UGO ETERIANO: FILOSOFIA MEDIEVALE O PENSIERO BIZANTINO?* -- DINAMICHE DI POTERE FRA TESTO E COMMENTO: LA COMPENDIOSA EXPOSITIO DEL DE SANCTO ET IMMORTALI DEO DI UGO ETERIANO -- THE MEDIEVAL SLAVONIC "DOSSIER" OF THE GREAT SCHISM: HISTORICAL NARRATIONS AND LISTS OF LATIN ERRORS AMONG THE BALKAN SLAVS -- THE DIPLOMACY OF THEOLOGICAL DEBATE: THE FRIARS' REPORT OF THE DISPUTATIO OF 1234 -- NICÉPHORE BLEMMYDÈS EN DIALOGUE THÉOLOGIQUE AVEC LES LATINS (1234-1250) -- WHY WAS THE FILIOQUE FORMULA CHANGED AT THE SECOND COUNCIL OF LYON (1274)?* -- LA LETTERA AI CIPRIOTI DEL PATRIARCA CALLISTO I.